Effects of Privatization and Ownership in Transition Economies - Estrin, Saul (2012)
The paper evaluates the effects of privatization in the post-communist economies and China. In post-communist economies privatization to foreign owners results in a rapid improvement in performance of firms, while performance effects of privatization to domestic owners are less impressive and vary across regions, coinciding with differences in policies and institutional development. In China relatively more estimates suggest that privatization to domestic owners improves the level of performance. Concentrated private ownership has a stronger positive effect on performance than dispersed ownership in the post-communist economies, but foreign joint ventures rather than wholly owned foreign firms have a positive effect in China. Worker or collective ownership does not have a negative effect. In the post-communist economies new firms are equally or more efficient than firms privatized to domestic owners, and foreign start-ups are more efficient than domestic ones. Privatization is not associated with lower employment. When accompanied by complementary reforms, privatization has a positive effect on economic growth. Three factors appear to drive the more positive effect of privatization to foreign than domestic owners. Domestic managers have more limited skills and access to world markets, domestically privatized firms have been more subject to tunneling and in some countries new large shareholders artificially decreased performance. The important policy implication is that privatization per se does not guarantee improved performance, at least not in the short- to medium-run. Type of private ownership, corporate governance, access to know-how and markets, and the legal and institutional system matter for firm performance.